Rewards and punishments: informal contracting through social preferences - Sylvain Chassang; Christian Zehnder (Theoretical Economics, 2016)
This paper develops a positive model of informal contracting in which rewards and punishments are not determined by an ex ante optimal plan but instead express the ex post moral sentiments of the arbitrating party. We consider a subjective performance evaluation problem in which a principal can privately assess the contribution of an agent to the welfare of a broader group. In the absence of formal contingent contracts, the principal chooses ex post transfers that maximize her social preferences. We characterize the incentives induced by the principal's preferences, contrast them with ex ante optimal contracts, and derive novel testable predictions about the way externalities are internalized in informal settings.
Keywords: C72; D23; D86; K13; K42; L20; 330; Informal contracts; social preferences; fairness; intent-based justice; subjective performance evaluation; no punishment without guilt